ANCA-Associated Vasculitis in Patient with CREST-Syndrome - Case Report - Zakharova EV; Makarova TA; Stolyarevich ES (Archives of Clinical Nephrology - Peertechz Publications, 2016)
Background: ANCA-associated vasculitis is a small vessel necrotizing vasculitis with few or no immune deposits, necrotizing glomerulonephritis is very common in the microscopic poliangiitis subset. Systemic scleroderma renal involvement is included neither in the current classification criteria, nor in the definition of CREST-syndrome. The presence of ANCA in patients with SS was first described in 1996, and since that has been reported to be rare and not presenting clinical significance. However during next decade about 50 cases with association of SS and AAV were described, and more recently, additional cases were reported and the clinical features of such association were recognized. Results: We present here a case, illustrating association of systemic sclerosis and ANCAassociated vasculitis, proven by kidney biopsy findings of sclerosing and necrotizing glomerulonephritris with11% of crescents. Conclusions: Patients with systemic sclerosis in general, and CREST-syndrome in particular, demonstrating unexplained deterioration of kidney function, should be tested for ANCA and undergo kidney biopsy in search for association with AAV. Immunosuppressive treatment, especially in cases with advanced sclerotic changes by kidney pathology evaluation, should be performed with caution to ensure patient's survival even in cases of progression to ESRD.